PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN - Anggun Meyrista Devi***, Yusron Rozzaid* Toni Herlambang** (JURNAL MANAJEMEN DAN BISNIS INDONESIA, 2015)
The purpose of this research is analysing the effect of compensation and motivation in collective or partial to the official employee satisfaction.The research uses the data of primary data which uses questioner method. The research population and the sample is including all the official employees of PT. Nusapro Telemedia Persada In Banyuwangi. There are 31 official employees as the sample in this research. Validity test, realibility, and double linier regression are used as the analysis tools in this research.The result of this research shows that compensation and motivation in colllective has the effect to the official employee satisfaction. And also in partial side, both of variabel compensation and motivation give the satisfaction effect to the official employee.